Following Physical Exertion Training by Taking Ginseng Capsules in the Development of Lactic Endurance and Achievement for 1500 m Young Runners - SABEEH KAREEM, WISAL; Jawad Mohammed, Zaydoon; HUSSEIN SAGHEER, ALI (International Journal of Psychosocial Rehabilitation, 2020)
The world is witnessing a development in various aspects of life as a result of the growth of scientific knowledge and practical laboratories and the reliance on various sciences and benefit from the results of studies and research in these fields, especially in the field of sports, which is currently witnessing development and progress in the digital achievements achieved both at the level of Arab, international and Olympic forums, and despite the scientific progress in the field of training, the functional adaptations that occur to the athlete as a result of continuing training and using the quality of exercises suitable the requirements of the athletics competition many and comprehensive for the members and functions of the athlete's body Especially the 1500-meter running competition with special physical specifications, foremost among which is the lactic endurance (Wang, 2007) And because the circumstances of those require the runner to be characterized by the status of lactic endurance, considering that the work falls within the system of axing (more than 3 minutes) so it is necessary for the trainers to develop the endurance of the runner through the events of changes in the organs and members of the athlete and from this basis the athlete to continue to perform despite the accumulation of lactic acid with his blood, the better the possibility of the athlete aerobic and anaerobic reflected directly on the level of physical and technical performance As nutrition science is now one of the applied sciences on which it depends in the field of physical education and sports, nutrition has been associated with exercise for health because it has an important role in weight control and control of body composition as it plays an important role in the ability of the athlete to withstand training and delay the onset of fatigue, (Qasim, 1990) As well as the speed of hospitalization, as evidenced by its important role in the competition to raise the level of physical performance. Since the capsules of the plant of the genosith plant is one of the most important medicinal plants that have an effect on many physiological and physical variables that are closely related to the physical and technical performance of the athlete , (Matthew, 2010) hence the importance of research in the development of lactic endurance and achievement of runners ran 1500 meters young through physical exercises to resist fatigue resulting from the accumulation of lactic acid and thus maintain the speed of performance for as long as possible during competition and training.